Challenging the vocational education and training for development orthodoxy - McGrath, Simon (2012)
The orthodox account of vocational education and training for development is firmly based in Neoliberal assumptions about the primacy of the economic. Yet, there are a range of alternative accounts of development, receiving increasing attention, that stress the importance of a wider vision of humanity and human development. At the same time, there are longstanding, though more marginal, traditions of seeing vocational education as having a moral purpose, linked to learning to becoming more human. This paper seeks to connect these two traditions to offer a new way of thinking about VET for development.